Virtual and Space Tourism as New Trends in Travelling at the Time of the COVID-19 Pandemic - Michał Roman; Robert Kosiński; Kumar Bhatta; Arkadiusz Niedziółka; Andrzej Krasnodębski (Sustainability, 2022)
The first European COVID-19 infection was recorded in February 2020, and Poland followed in mid-March. Restrictions were imposed on traveling between states and using public space. These movement restrictions forced a search for new, often innovative, forms of tourism. Google Earth virtual reality (VR), Google Street View, and the Chernobyl VR Project are just some of the selected opportunities to create virtual tours. Different activities using VR mean that people can experience the illusion of travelling in time and space, outside of their everyday surroundings, in a digitally constructed three-dimensional (3D) environment, for cognition or entertainment. Therefore, this study aimed to present virtual and space tourism as new traveling trends during various crises, such as health, economic, etc. A diagnostic survey with a developed questionnaire was conducted in June and July 2021 in Poland. A total of 564 fully answered responses were collected from randomly selected respondents. We found that around 82% of Polish people were aware of VR technology, and 70% believed that new technologies determine VR tourism development. VR presents the possibility of travelling to places that no longer exist in their original form, but have been reconstructed only in VR. Around 75% of the respondents agreed that VR tourism plays an essential role in tourism promotion in Poland and throughout the world. Moreover, VR and augmented tourism lets us visit fictitious and dangerous, politically restricted, and geographically as well as economically difficult destinations. For example, our results revealed that many people want to experience North Korea, the USA, Antarctica, Syria, etc. At the same time, people recommended the NASA space station as a visiting destination using VR and augmented reality. VR offers an alternative form of tourism during crises and pandemics such as COVID-19. We found over 26% of the respondents were satisfied with contemporary tourists’ cognitional needs during VR sightseeing. More than 87% of the ...